2023
DOI: 10.3389/fpls.2022.1094459
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs and lncRNAs in tomato: Roles in biotic and abiotic stress responses

Abstract: Plants are continuously exposed to various biotic and abiotic stresses in the natural environment. To cope with these stresses, they have evolved a multitude of defenses mechanisms. With the rapid development of genome sequencing technologies, a large number of non-coding RNA (ncRNAs) have been identified in tomato, like microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). Recently, more and more evidence indicates that many ncRNAs are involved in plant response to biotic and abiotic stresses in tomato. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 125 publications
0
4
0
Order By: Relevance
“…miR398 is a highly conserved miRNA that is widespread in angiosperms [29] and is considered a master regulator of developmental and environmental stress responses [53,65]. Although miR398 has been described as induced by P. infestans inoculation in the tomato [66], we have seen that it is downregulated in T11-treated plants, as occurred in the typical responses of tomato plants tolerant to abiotic stresses [45,67]. Moreover, the expression of a putative miR398 target gene, encoding an NLR protein, did not show expression changes in T11-treated plants, suggesting that this type of immune response does not seem to be activated 30 days after the application of T. atroviride.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…miR398 is a highly conserved miRNA that is widespread in angiosperms [29] and is considered a master regulator of developmental and environmental stress responses [53,65]. Although miR398 has been described as induced by P. infestans inoculation in the tomato [66], we have seen that it is downregulated in T11-treated plants, as occurred in the typical responses of tomato plants tolerant to abiotic stresses [45,67]. Moreover, the expression of a putative miR398 target gene, encoding an NLR protein, did not show expression changes in T11-treated plants, suggesting that this type of immune response does not seem to be activated 30 days after the application of T. atroviride.…”
Section: Discussionmentioning
confidence: 63%
“…This would indicate that plant defenses would be dormant after one month of T. atroviride application. According to previous studies in tomato plants, downregulated miRNAs, such as miR5300 and miR6024, are related to tolerance to Botrytis, Fusarium, Alternaria, and Phytophthora pathogens [45,[72][73][74]. Moreover, the miR6024-NLR interaction facilitates necrotrophic pathogenesis by Alternaria solani in the tomato [75].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, investigating the role of the HS master regulator HsfA1a, they found that it plays a key role in the dynamic formation of promoter-enhancer contacts and in controlling the transcriptional response at the onset of HS. Recently, more emerging ncRNAs have been found to play important roles in HS response ( Ding et al., 2020 ; Li et al., 2023 ). This RNA class does not encode a protein and involves microRNAs (miRNAs), small interfering RNAs (siRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs).…”
Section: Epigenetic Post-transcriptional and Post-translational Regul...mentioning
confidence: 99%
“…The involvement of cir-cRNA in biotic stress is evident and explored with more plant-microbe interaction studies. The involvement of circRNA in both biotic and abiotic stress has also been documented in tomato [33]. Studies of the in-depth mechanistic roles, interaction pattern, and mode of action with other immunogenic modules are urgently necessary to unravel the mystery behind this repertoire of non-coding molecules.…”
Section: The Roles Of Circrna In Biotic Stress Tolerance Circuitry In...mentioning
confidence: 99%